Supplementation of Garcinia mangostana Linn and Vasconcellea pubescens A.DC extract reduced exercise-induced oxidative stress in rats - Heru Sasongko; Sugiyarto Sugiyarto; Renita Wahyu Nur Hidayati; Bayu Anggoro Saputro (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
The objective of this study was to see how supplementation with Garcinia mangostana extract (GME) and Vasconcellea pubescens extract (VPE) affected exercise performance and oxidative stress in intensely exercised rats. Twenty-five male rats were used in the study. Rats were divided into five groups: normal, stress oxidative control, combination GME:VPE (50:50), combination GME:VPE (75:25), and combination GME:VPE (25:75) groups. The antioxidant activity of a single extract from the literature was used to make the percentage comparison between extracts. The chronic exercise was done by swimming at 10 m/day for two weeks. Rats in the acute exercise groups were treated by swimming on the pail containing water. Blood samples were collected from the orbital sinus to determine hematological parameters. Liver tissue samples for the analysis of malondialdehyde (MDA) and glutathione (GPx) markers. Data analysis was performed statistically using One Way ANOVA. The combination of GME and VPE was shown to be effective in reducing oxidative stress and increasing MDA and GPx enzyme activity. The administration of both extracts also showed changes in the hematological profile.